Prevalence and Factors Associated with Sexually Transmitted Infections among Jimma University Students, Southwest Ethiopia - Rahel Tamrat; Tesfaye Kasa; Zewdineh Sahilemariam; Mulatu Gashaw (International Journal of Microbiology)
Background. Globally, one-third of new sexually transmitted infection (STI) cases occur in people under 25 years of age every year. University students are in the youth age category and are exposed to risky sexual behaviors such as unprotected sexual intercourse leading to STIs. Therefore, this study was aimed to assess the prevalence and associated factors of STI among Jimma University students. Method. A health facility-based cross-sectional study was conducted at Jimma University students’ clinic from April 2017 to October 2017 among students with STI syndromes. Urethral, endocervical, and vaginal discharge swabs were collected by attending nurses. Standard protocol was followed to detect the etiologies of STI. Data were entered and analyzed using SPSS Version 20. Results. The overall prevalence of STIs among clinically suspected university students was 14.3%. The predominant causes of STI were Neisseria gonorrhoeae (7.4%) followed by T. vaginalis (4.8%) and T. pallidum (3.7%). Having had sex after taking alcohol was significantly associated with STIs (P≤0.000). All N. gonorrhoeae isolates were found to be resistant to penicillin and tetracycline. Conclusion. In this study, the prevalence of STI was relatively high. The isolated N. gonorrhoeae was resistant to commonly prescribed antibiotics. Therefore, evidence-based treatment and proper reproductive health education for youth are highly recommended.